2000
DOI: 10.1002/(sici)1097-0142(20000515)88:10<2283::aid-cncr12>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Papanicolaou smear history and diagnosis of invasive cervical carcinoma among members of a large prepaid health plan

Abstract: BACKGROUND Despite the widespread use of Papanicolaou (Pap) smear screening, substantial morbidity and mortality from cervical carcinoma continue in the U.S. Although access to screening is a major barrier to use of the Pap smear, invasive cervical carcinoma (ICC) still is observed in health plan members who have comprehensive preventive care coverage. METHODS For all women diagnosed with ICC between 1988 and 1994 in a large prepaid health plan, the authors retrospectively reviewed the medical records for pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(53 citation statements)
references
References 26 publications
3
47
0
3
Order By: Relevance
“…Women who do not attend CCS have a greater risk of developing cervical cancer [8,9]. As a result, much research in the area focuses on factors influencing CCS attendance and strategies aiming to increase CCS participation.…”
Section: Introductionmentioning
confidence: 99%
“…Women who do not attend CCS have a greater risk of developing cervical cancer [8,9]. As a result, much research in the area focuses on factors influencing CCS attendance and strategies aiming to increase CCS participation.…”
Section: Introductionmentioning
confidence: 99%
“…Without exception, the major finding from these exercises previously is that a significant proportion of women with invasive cervical cancer are either not screened or underscreened. [9][10][11][12][13] The New Zealand National Cervical Screening Programme (NCSP) was established in 1990 and recommends routine three yearly screening of all women aged 20-70 years. The NCSP is nationally organised and co-ordinated, but there is no national register of eligible women to ensure that all are invited and recalled at appropriate intervals for cervical smears.…”
Section: Introductionmentioning
confidence: 99%
“…9 Other studies have confirmed that population coverage is vital for success and that women who participate are well protected from cervical cancer. 10,11 For Swedish women aged 23-50, coverage of screening, including opportunistic smears taken outside the screening program, was 78% during a 3.5-year period ending 2009. 12 This is high coverage in an international context, 13 but regional differences are substantial (range 64-91%).…”
mentioning
confidence: 99%